Peran pengalaman pelanggan dalam memediasi pengaruh kualitas layanan, citra perusahaan, dan harga terhadap loyalitas pelanggan PT. Pos Indonesia - Diyah Ayu Patmawati; Anik Lestari Andjarwati (Jurnal Ilmu Manajemen, 2023)
This paper analyses the effect of service quality, corporate image, and price on customer loyalty by using customer experience as a mediating variable. This research uses quantitative data. The sampling technique used was non-probability sampling with the type of purposive sampling. The sample used in the study is 220 respondents. The research method used path analysis and data collection through questionnaires. The results showed that service quality and price positively and significantly affected customer loyalty. Corporate image has no significant effect on customer loyalty. Service quality, corporate image, and price have a positive and significant effect on customer experience, and the effect is greater when going through customer experience variables. Pos Indonesia is expected to continue to develop and improve the quality of its services, especially in the special express post service, maintain and improve its corporate image, provide customers with affordable prices and provide more benefits to customers to enhance their loyalty.